Pengaruh self efficacy dan organizational trust terhadap employee performance melalui employee engagement - Wizarotul Maliyah, Arrum; Budiono (Jurnal Ilmu Manajemen, 2024)
This research aims to determine the influence of self-efficacy and organizational trust on employee performance through employee engagement at employees of PT. XYZ. This research is causality research with a quantitative approach. The sampling technique used a saturated sampling technique with a sample of 91 permanent employees of PT. XYZ. The statistical analysis used is partial least squares (PLS) with the help of SmartPLS 3 software. The results of this study explain that self efficacy has no significant effect on employee performance, self efficacy has a positive and significant effect on employee engagement, organizational trust has a positive and significant effect on employee performance, organizational trust has a positive and significant effect on employee engagement, employee engagement has a positive and significant effect on employee performance, self efficacy influences employee performance through employee engagement, and organizational trust influences employee performance through employee engagement.